2021
DOI: 10.3390/polym13162648
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage Delivery Systems Based on Composite PolyHIPE/Nanocellulose Hydrogel Particles

Abstract: The role of bacteriophage therapy in medicine has recently regained an important place. Oral phage delivery for gastrointestinal treatment, transport through the stomach, and fast release in the duodenum is one of such applications. In this work, an efficient polyHIPE/hydrogel system for targeted delivery of bacteriophages with rapid release at the target site is presented. T7 bacteriophages were encapsulated in low crosslinked anionic nanocellulose-based hydrogels, which successfully protected phages at pH &l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 60 publications
(78 reference statements)
1
17
0
Order By: Relevance
“…28 The n value of the EGF-doped nano films was 1.73, while the value of the EGF-doped flat films was 1.66, indicating that anomalous transport occurred owing to Fickian diffusion and polymer relaxation as the films swelled. 29…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…28 The n value of the EGF-doped nano films was 1.73, while the value of the EGF-doped flat films was 1.66, indicating that anomalous transport occurred owing to Fickian diffusion and polymer relaxation as the films swelled. 29…”
Section: Resultsmentioning
confidence: 99%
“…28 The n value of the EGF-doped nano films was 1.73, while the value of the EGF-doped flat films was 1.66, indicating that anomalous transport occurred owing to Fickian diffusion and polymer relaxation as the films swelled. 29 Several reports discussed the toxicity of excessive EGF levels both for in vitro and in vivo studies. 27,30,31 In particular, the report by Ramineni and coworkers successfully demonstrated that a concentration regime between 1-5 ng mL −1 EGF provided maximal cell migration, cellular differentiation and wound healing.…”
Section: Biomaterials Science Papermentioning
confidence: 99%
“…Further, breakdown in the DNA repair process facilitates the induction of colorectal cancer 21 Salmonella typhimurium 22 The bacterium produces AvrA protein that results in the proliferation of the IL-8 intestinal epithelial cell lining, thereby facilitating the induction of colorectal cancer 22 The cease in proliferation in the growth of the gut microbiome resulting in dysbiosis is carried out by certain bacteriophages specific to the gut microbiome. 23 Phage M13 23 Bacteroides fragilis (Enterotoxigenic) 24 Phage VA7 24 Escherichia coli 15,16,25 Phage T7 25 , Phage ZCEC5 16 , Phage T4…”
Section: Gut Microbiome Associated With Colorectalmentioning
confidence: 99%
“…28−32 To date, porous clay, 33 mineralbased materials, 14 metallic foams, 34 porous carbon, 35 and porous polymers 36,37 are the most commonly used framework materials for shape-stabilized PCM. High internal phase emulsion templated polymers (PHP) as porous polymers have been used in a wide variety of applications such as adsorption, 38,39 purification, 40,41 separation, 42 controlled release, 43,44 and scaffolding, 45 and there is limited research in energy storage application. 46,47 Recently, porous PHP foams have begun to gain attention for the stabilization of PCMs owing to their superior features such as shape stabilization, enclosure ability, high loading rate, excellent structural stability, and interpenetrating pore morphology.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these limitations, in addition to PCM microcapsules, the application of shape-stable porous materials as a PCM carrier has received great interest in the literature. To date, porous clay, mineral-based materials, metallic foams, porous carbon, and porous polymers , are the most commonly used framework materials for shape-stabilized PCM. High internal phase emulsion templated polymers (PHP) as porous polymers have been used in a wide variety of applications such as adsorption, , purification, , separation, controlled release, , and scaffolding, and there is limited research in energy storage application. , Recently, porous PHP foams have begun to gain attention for the stabilization of PCMs owing to their superior features such as shape stabilization, enclosure ability, high loading rate, excellent structural stability, and interpenetrating pore morphology. PHPs are monolithic, controllable, highly porous polymers with low density, high specific surface area, highly cross-linked polymer matrix, the porosity of which is created by the continuous phase of emulsions. PHPs in particular stand out for their large gaps bounded by small windows on the skeleton.…”
Section: Introductionmentioning
confidence: 99%